Nursing of a patient with acute cerebral infarction combined with lower gastrointestinal tract bleeding (1例急性脑梗死并发下消化道出血患者的护理体会) - CHEN Haixiang (陈海香); WU Min (吴敏) (中西医结合护理)
This paper summarized the nursing management of a patient with acute cerebral infarction combined with lower gastrointestinal tract bleeding. Hemostasis, fluid infusion and transfusion therapy were carried out initially. Nursing staff focused on basic nursing, medication guidance and psychological care during the treatment. Based on the Traditional Chinese Medicine syndrome differentiation, Traditional Chinese Medicine nursing technology including acupoint scrapping, meridian massage, emotional care were carried out to improve patient’s treatment compliance and recovery. (本文总结 1例急性脑梗并发下消化道出血患者的护理经验。首先积极开展止血、补液、输血治疗, 以补充血容量和抗休克。在此基础上开展中西医结合护理, 做好基础护理、用药指导、心理护理, 遵循中医辨证施护原则, 给予穴位刮痧、经络按摩、情志护理等中医护理适宜技术干预, 有效提高患者治疗依从性, 促进患者康复。)